2013
DOI: 10.1126/scitranslmed.3006086
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Mutational Signatures of Aristolochic Acid and Its Application as a Screening Tool

Abstract: Aristolochic acid (AA), a natural product of Aristolochia plants found in herbal remedies and health supplements, is a group 1 carcinogen that can cause nephrotoxicity and upper urinary tract urothelial cell carcinoma (UTUC). Whole-genome and exome analysis of nine AA-associated UTUCs revealed a strikingly high somatic mutation rate (150 mutations/Mb), exceeding smoking-associated lung cancer (8 mutations/Mb) and ultraviolet radiation-associated melanoma (111 mutations/Mb). The AA-UTUC mutational signature was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
260
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(278 citation statements)
references
References 48 publications
17
260
1
Order By: Relevance
“…The predominance of A4T transversion on the non-transcribed strand of DNA along with a preference for deoxyadenosine in the C/T[A:T]A/G motif supports exposure to AA as the underlying factor. Similar patterns have recently been observed in urothelial carcinoma of the upper urinary tract in patients 12,27 as well as in cultured primary cells 27,28 exposed to AA, with C/T[A:T]G being the preferential sequence context. Our WGS data show that a less marked increase in A4T transversions also occurs in other sequence contexts.…”
Section: Discussionsupporting
confidence: 56%
“…The predominance of A4T transversion on the non-transcribed strand of DNA along with a preference for deoxyadenosine in the C/T[A:T]A/G motif supports exposure to AA as the underlying factor. Similar patterns have recently been observed in urothelial carcinoma of the upper urinary tract in patients 12,27 as well as in cultured primary cells 27,28 exposed to AA, with C/T[A:T]G being the preferential sequence context. Our WGS data show that a less marked increase in A4T transversions also occurs in other sequence contexts.…”
Section: Discussionsupporting
confidence: 56%
“…The ICC-unique mutation spectrum (CTG4CAG and CAG4CTG) is tightly associated with liver inflammation, fibrosis and cirrhosis, suggesting that mutagens that have caused such mutations have also caused inflammation, fibrosis and cirrhosis. It is also likely that these ICC patients who harbour the ICC-unique mutation spectrum may have been exposed to aristolochic acid (AA), a nitrophenanthrene carboxylic acid found in all members of the genus Aristolochia plants that have been used in medicine for over 2,000 years 65,66 . Recent studies showed that humans exposed to AA causes A:T4T:A transversions 65,66 .…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that these ICC patients who harbour the ICC-unique mutation spectrum may have been exposed to aristolochic acid (AA), a nitrophenanthrene carboxylic acid found in all members of the genus Aristolochia plants that have been used in medicine for over 2,000 years 65,66 . Recent studies showed that humans exposed to AA causes A:T4T:A transversions 65,66 . AA has been demonstrated to be a causative carcinogen of urothelial carcinoma of the upper urinary tract (UTUC) 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of human bronchial cells to the diol epoxide of the PAH benzo[a]pyrene causes DNA damage at the same G:C pairs that are frequently mutated into T:A in lung cancers from smokers (Denissenko et al 1996;Tretyakova et al 2002). Recently, a mutational fingerprint of aristolochic acid has been reported in urothelial carcinomas of subjects with a history of exposure to herbal remedies and food products containing seeds of Aristolochia clematitis (Hollstein et al 2013;Poon et al 2013). Last, all cancer types harbor at least 20% of G:C.A:T mutations at hypermutable CpG dinucleotides, attributed to the normal cellular event of deamination of 5-methylcytosine to thymine.…”
Section: Mutation Patterns As Signatures Of Mutagenic Processesmentioning
confidence: 99%